Prevention of Gastric Cancer: Helicobacter pylori Treatment - Ji Yong Ahn (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2024)
Helicobacter pylori infection has been associated with various gastric diseases, including ulcers, adenomas, and adenocarcinomas. Over 40 years since the discovery of H. pylori, numerous studies have shown that H. pylori eradication therapy can help prevent gastric cancer not only in healthy individuals but also in patients who have already been treated for early gastric cancer. Moreover, some studies have shown that eradication therapy can improve gastric mucosal inflammatory diseases, such as atrophic changes and intestinal metaplasia. This article reviews the epidemiology of H. pylori infections and gastric cancer, mechanisms of H. pylori-associated gastric cancer development, and current evidence supporting the benefits of H. pylori eradication for reducing or preventing gastric cancer.